FORMULASI SEDIAAN GEL EKSTRAK ETANOL DAUN KEMANGI (Ocimum sanctum L.) DENGAN AMYLUM MANIHOT SEBAGAI GELLING AGENT - Wicahyo, Septian Maulid; Fauzi Rifqi Pramita (Universitas Duta Bangsa Surakarta, 2024)
Basil leaves (Ocimum sanctum L.) contain bioactive compounds such as flavonoids, tannins, and saponins that have the potential as antibacterials and antioxidants. This study aims to formulate a gel preparation of basil leaf ethanol extract with manihot starch as a gel-forming agent, and to evaluate the physical characteristics and stability of the gel. The results showed that the formula with a concentration of 3% manihot starch gave optimal results in viscosity, pH, and gel spreadability. Stability tests showed that the gel remained stable during 28 days of storage at room temperature. This study proves the potential use of manihot starch as a natural alternative in gel formulation.